Leadership and SEN : meeting the challenge in special and mainstream settings - Burnett, Nick (David Fulton, 2005)
"How are we to make our schools into outward-looking centres of excellence? In his efforts to answer this question, Nick Burnett uses several schools - and their cutting-edge leaders - as case studies and looks at how they have responded successfully to the challenges of recent legislation and guidelines." "For special school leaders and prospective leaders, those involved in making decisions about specialist provision and anyone delivering training and support to these professionals."--Jacket